Konsumsi Zat Gizi Makro Pada Balita Stunting (24-59 Bulan) - Desy Zulia Isnainy; Fifi Luthfiyah; Lalu Khairul Abdi; Reni Sofiyatin (Jurnal Gizi Prima (Prime Nutrition Journal), 2017)
Background. Stunting is very short state of body so that the deficit exceeded -2 SD below the median length or height that became an international reference population (Gibney, Michael J, et al. 2013). Based on the results of RISKESDAS 2013 the proportion of stunting tends to be high in children 24-59 months. The results of the Nutritional Status Monitoring (PSG) West Lombok in 2013 showed Gunung Sari is the region with the highest prevalence of stunting in West Lombok is 58.78%, the prevalence increased from 2012 in the amount of 53.65%.Research Methods. This study used is descriptive observational research. Measurement of the level of consumption is done with a 24-hour recall method and compared with the needs of the sample.Research Result. Respondents in this study is 16 people. Respondents aged 20-35 years amounted to 81.25% (13 people), elementary education level of 37.50% (6 people) and SMP amounted to 37.50% (6 people). Respondents who worked 56.25% (9 people). Revenue from family toddler <UMR (62.5%). The samples in this study is 16 samples, consisting of 11 men and 5 women. The highest incidence of stunting in the age group 48-59 months amounted to 68.75% (11 people) with male gender is 68.75% (11 people). The distribution of the nutritional status based on the index TB/U are short and very short categories respectively by 50% (8 people). The incidence of infection in infants either diarrhea or fever mostly classified namely diarrhea rarely amounted to 87.5% (14 people) and a fever of 56.25% (9 people).  macro nutrients intake does not describe that the macro-nutrient intake as a risk factor stunting.Conclusion. macro nutrients intake does not describe that the macro-nutrient intake as a risk factor stunting.